"Inappropriate" Subjects: The Portrayal of Women in Sri Lanka's Parliamentary Discourse - Wijewardene, Shermal; Peiris, Pradeep (University of Colombo, 2015)
This paper explores the portrayal of women in Sri Lanka's parliamentary speeches, focusing in particular on the role of the former Minister of Child Development and Women's Affairs, Mr Tissa Karaliyadda, in instantiating certain ways of talking about the subject 'women' and the issues concerning them. This exploration provides important, although not exhaustive, insights into how women are perceived and talked about in the country's legislature. The corpus will consist of Hansards that report the former Minister's interventions, dating from his appointment in 2010 and extending to 2014. The paper takes a discourse analysis approach from the position that parliamentary speech is not just communication in any self-evident sense, but reflects a specific ordering of language and signification within a social institution, and is underpinned by an institutional basis of power.
Keywords: Women, Parliamentary discourse, Development, Inappropriate